Dampak Kinerja Keuangan terhadap Profitabilitas Bank Syariah: Analisis Perbandingan Bank Syariah di Indonesia dan Malaysia - Haris, Dea Aryandhana Mulyana; Huda Nasution, Akmal; Nurul Fakhri, Ulumuddin; Bustami, Abiyajid (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the effect of financial performance on the profitability of Islamic banks in Indonesia and Malaysia, using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach and secondary data from 2019 to 2023. The results showed that asset quality, as measured by Net Performing Financing, proved to have a significant influence on profitability, with the coefficient value of Islamic banks in Indonesia is 0.035 and in Malaysia is 0.05. While other factors do not have a significant effect on profitability. This shows that both Islamic banks are very vulnerable to the quality of financing. Based on the results of this study, it is expected that stakeholders, such as Islamic banks and the government, can take concrete steps to improve the profitability and stability of the Islamic banking sector. Islamic banks are expected to focus on improving asset quality, managing credit risk better, and developing effective risk management strategies. Keywords: Financial performance; Profitability; Islamic banks; Indonesia; Malaysia; PLS-SEM.